Quelles interventions humanitaires internationales pour la reconstruction ? - Simon Veitl (EchoGéo)
Post-disaster international aid builds its action on standards (UNDRR frameworks, GAR), applied by stakeholders (UN, state and NGO), who organize themselves through a specific governance model (the cluster tool) and define a strategy to rebuild the land. In this study, we will do a critical analysis of this intervention. We will use the renovation of school buildings in the “Sud” department of Haiti after Hurricane Matthew in 2016 as an example. Throughout the analysis of the social and geographical impact of this model, we will see how the reconstruction model is trying to lead the land towards resilience and sustainable development. We will also see how, in practice, this injunction of adaptation is facing realities.